ANALISIS PENGARUH CORPORATE RISK DISCLOSURE TERHADAP BIAYA MODAL EKUITAS DAN KINERJA PERUSAHAAN (Studi Empiris pada Perusahaan Perbankan yang Terdaftar di Bursa Efek Indonesia Periode 2015 – 2017) - Desi Nofianti Cornelia; Muchamad Syafruddin (Diponegoro Journal of Accounting, 2019)
The aim of this study is to examine the effect of corporate risk disclosure on cost of equity capital and firm perfomance. This study used systematic risk,market to book ratio, leverage, firm size, audit committee independen, and auditors type  as control variable. The population in this study consists of financial firm especially the banking sektor in Indonesia Stock Exchange for the period 2015 - 2017. Sample determined with purposive sampling method. Total sample of this research is 102 companies.This study used multiple regression analysis for hypotheses testing. The results of this study show that corporate risk disclosure has a negative effect on cost of equity capital and corporate risk disclosure has positive effect on firm perfomance.